Obestatin alleviates subarachnoid haemorrhage-induced oxidative injury in rats via its anti-apoptotic and antioxidant effects - ŞENER, AZİZE; YEGEN, BERRAK; AKAKIN, DİLEK; ÖZSAVCI, DERYA; ŞENER, GÖKSEL; BİNGÖL ÖZAKPINAR, ÖZLEM (TAYLOR & FRANCIS LTD, 2013)
Objective: The aim was to investigate the putative anti-inflammatory and anti-apoptotic effect of obestatin in a rat model of subarachnoidal haemorrhage (SAH). Methods: To induce SAH, rats were injected with 0.3 mL blood into their cisterna magna. At 48 hours rats were decapitated after neurological examination. Blood-brain barrier (BBB) permeability, brain water content, oxidative stress markers and histological analysis were done in brain tissue. Results: The results showed that neurological examination scores were increased in the SAH group and, moreover, BBB permeability was impaired and oedema formed. SAH resulted in increased levels of plasma tumour necrosis factor (TNF)-alpha, interleukin (IL)-1 beta, IL-6 levels and caspase-3 activity. Lipid peroxidation and protein oxidation levels and myeloperoxidase activity were all increased in the brain tissue, with concomitant decreases in antioxidant enzymes. On the other hand, SAH-induced neurological impairment and oxidative brain injury were ameliorated in the obestatin-treated group. Conclusion: The present study provides the first evidence that peripheral administration of obestatin exerts potent anti-inflammatory and neuroprotective effects in SAH-induced oxidative damage by maintaining a balance in oxidant-antioxidant status through the augmentation of endogenous antioxidants and the inhibition of pro-inflammatory mediators.
Keywords: Apoptosis; obestatin; oxidative; stress; subarachnoid haemorrhage; BLOOD-BRAIN-BARRIER; COGNITIVE DYSFUNCTION; MESSENGER-RNA; GHRELIN; EXPRESSION; VASOSPASM; DAMAGE; STRESS; OXYHEMOGLOBIN; PROTECTS